Pengaruh Tingkat Pendidikan, Pemahaman Akuntansi dan Sosialisasi SAK EMKM terhadap Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM - Salsabila Rohmatus Zahroh; Mega Rosdiana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research was conducted to determine the influence of education level, understanding of accounting and socialization of SAK EMKM on the preparation of SAK EMKM-based MSME financial reports. The data used in this research is primary data collected through distributing questionnaires with Likert scale measurement techniques. This research was conducted in Sawahan District. The population in this research is all MSMEs in Sawahan Regency, totaling 138 MSME actors. The sample was selected using a purposive sampling technique and calculated using the Slovin formula so that the total sample was 58 MSME actors. Data analysis techniques consist of descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression tests and hypothesis tests with the help of IBM SPSS Statistics 25. The results of the research show that each variable of education level, understanding of accounting and socialization of SAK EMKM has a positive effect towards the preparation of SAK-EMKM based MSME financial reports. This can be interpreted as meaning that all the variables used can influence MSME actors in preparing financial reports based on SAK-EMKM